Toll Like Receptors as Sensors of the Tumor Microbial Dysbiosis: Implications in Cancer Progression - Le Noci, Valentino; Bernardo, Giancarla; Bianchi, Francesca; Tagliabue, Elda; Sommariva, Michele; Sfondrini, Lucia (Frontiers in Cell and Developmental Biology, 2021)
The microbiota is a complex ecosystem of active microorganisms resident in the body of mammals. Although the majority of these microorganisms resides in the distal gastrointestinal tract, high-throughput DNA sequencing technology has made possible to understand that several other tissues of the human body host their own microbiota, even those once considered sterile, such as lung tissue. These bacterial communities have important functions in maintaining a healthy body state, preserving symbiosis with the host immune system, which generates protective responses against pathogens and regulatory pathways that sustain the tolerance to commensal microbes. Toll-like receptors (TLRs) are critical in sensing the microbiota, maintaining the tolerance or triggering an immune response through the direct recognition of ligands derived from commensal microbiota or pathogenic microbes. Lately, it has been highlighted that the resident microbiota influences the initiation and development of cancer and its response to therapies and that specific changes in the number and distribution of taxa correlate with the existence of cancers in various tissues. However, the knowledge of functional activity and the meaning of microbiome changes remain limited. This review summarizes the current findings on the function of TLRs as sensors of the microbiota and highlighted their modulation as a reflection of tumor-associated changes in commensal microbiota. The data available to date suggest that commensal “onco-microbes” might be able to break the tolerance of TLRs and become complicit in cancer by sustaining its growth.